Congenital Heart Disease and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Risk factors for inattention, hyperactivity and impaired school performance were examined in 109 children, 5 to 10 years of age, who had undergone newborn cardiac surgery for complex congenital heart disease (CHD) at Children's Hospital of Philadelphia, PA.